FIH-dependent asparaginyl hydroxylation of ankyrin repeat domain-containing proteins. - Cockman, M; Webb, J; Ratcliffe, P (2009)
Studies on hypoxia-sensitive pathways have identified a series of Fe(II)-dependent dioxygenases that regulate hypoxia-inducible factor (HIF) by prolyl and asparaginyl hydroxylation. The asparaginyl hydroxylase factor inhibiting HIF (FIH) targets a conserved asparaginyl residue in the C-terminal transactivation domain of HIF-alpha. This modification suppresses HIF transcriptional activity by inhibiting co-activator recruitment. Recent work has demonstrated that FIH targets an alternative class of substrate. Proteins containing a common interaction motif known as the ankyrin repeat domain (ARD) have been shown to be efficiently hydroxylated by FIH. This review aims to summarize what is currently known regarding ARD hydroxylation, including the kinetics and determinants of FIH-mediated ARD hydroxylation, the structural and functional consequences of ARD hydroxylation, and the potential for cross-talk between ARD proteins and HIF signaling.